ATYPICAL AUTISM IN CHILDREN: THE SPECIFIC FEATURES OF THEIR SOMATIC AND NEUROLOGICAL STATUS AND OUTPATIENT FOLLOW-UP BY A GENERAL PEDIATRICIAN - M. Yu. Bobylоva; I. V. Vinyarskaya; K. Yu. Bystrova; Yu. K. Narovatkina (Русский журнал детской неврологии, 2015)
Autism spectrum disorders in children are attracting the increasing attention of general practitioners, which is due to the specification of diagnostic criteria and to the recognition of the fact that there is atypical autism that is a syndrome of many different diseases. The authors consider in detail the theory of autism and the clinical manifestations of atypical autism, including possible neurological and somatic disorders. Individual attention is placed on the association of autistic disorder with epilepsy or epileptiform activity on the electroencephalogram. An emphasis is made on the need for an interdisciplinary approach and on the interaction of clinicians of different specialties when treating patients with autistic disorder.